Monoterpenoids Induce Agonist-Specific Desensitization of Transient Receptor Potential Vanilloid-3 (TRPV3) ion Channels - Muhammad Azhar Sherkheli; Heike Benecke; Julia Franca Doerner; Olaf Kletke; A. K. Vogt-Eisele; Guenter Gisselmann; Hanns Hatt (Frontiers Media S.A., 2009)
Transient receptor potential vanilloid-3 (TRPV3) is a thermo-sensitive ion channel expressed in skin keratinocytes and in a variety of neural cells. It is activated by warmth as well as monoterpenoids including camphor, menthol, dihydrocarveol and 1,8-cineol. TRPV3 is described as a putative nociceptor and previous studies revealed sensitization of the channel during repeated short-term stimulation with different agonists. In the present investigation TRPV3 was transiently expressed in either Xenopus oocytes or HEK293 cells. Whole-cell voltage-clamp techniques were used to characterize the behavior of TRPV3 when challenged with different agonists. Similarly, a human keratinocyte-derived cell line (HaCaT cells) was used to monitor the behavior of native TRPV3 when challenged with different agonists. We report here that prolonged exposure (5-15 minutes) of monoterpenoids results in agonist-specific desensitization of TRPV3. Long-term exposure to camphor and 1,8-cineol elicits desensitizing currents in TRPV3 expressing oocytes, whereas the non-terpenoid agonist 2-APB induces sustained currents. Agonist-specific desensitization of endogenous TRPV3 was also found in HaCaT cells, which may be taken as a representative for the native system. Terpenoids have a long history of use in therapeutics, pharmaceuticals and cosmetics but knowledge about underpinning molecular mechanisms is incomplete. Our finding on agonist-induced desensitization of TRPV3 by some monoterpenoids displays a novel mechanism through which TRP channels could be functionally modulated. Therefore, we conclude that desensitization of TRPV3 channels might be the molecular basis of action for some of the medicinal properties of camphor and 1,8-cineol.